First Hands-On Experience with the Application of a Newly Designed Double-Branched Thoracic Catheter for Thoracic Interventions - Müller-Arnecke, Dominik (The Thoracic and Cardiovascular Surgeon, 2017)
Background We investigated the technical handling of a y-shaped double-branched thoracic catheter with the aim of combining the effect of two separate catheters and the ease of use of a single one.Methods A total of 20 catheters were placed consecutively in 20 patients.Results In all patients, it was technically simple to position the catheter, whether in open or video-assisted surgery. The handling during removal corresponded to that of a single drain.Conclusion This type of drain appears to hold a lot of potential compared with the use of a single drain. Further studies with defined and larger patient populations should be performed.
Keywords: chest tube; air leak; catheter